HAMBATAN EKSPOR SAYURAN ORGANIK RIAU KE SINGAPURA - Pratiwi, Haryani Intan; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The purpose of this research is to explain obstacles of the cooperation Riau Province and Singapore in Organic Agriculture especially organic vegetable. The first time, both of countries signed Memorandum of Understanding in October 2001. The core of agreement is that Riau Province will export organic vegetable to Singapore as one country which has big potential vegetable market. Position of Singapore adjacent to Indonesia to provide advantages for Indonesia. Easy transport links made production costs low so that the larger profits earned by both of countries. In 2004-2008 the export of organic vegetables to Singapore Riau smoothly, and then vacuum caused due to a problem. And in 2014 Riau conduct re-export, but only lasted two months, namely in February and March. After that the export vacuum until now. This research applies pluralism perspective which considers that the state is not the only actor who plays a role in international relations, including in international trade transactions. As directives in this research, the author establishes nation-state as the level of analysis in this study. In accordance with the fact that the main object of international relations is the nation-state. And The theory used in this research is the theory of comparative advantage. This research applies research methods and literature (Library Research). The data in this study consisted of primary data and secondary data. Primary data was conducted by interview and observation. Secondary data were obtained from a collection of readings, namely: books, documents, internet and other readings that are related to the issues discussed. Keywords : Organic agriculture, pluralism perspective, comparative advantage